Analysis of Human Development Concept in Islamic Perspective Based on Al-Qur’an - Ezif Rizqi Imtihana; Diah Wahyuningsih; Restiana Restiana (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This study aims to analyze concept of human development from an Islamic perspective, focusing on characteristics of development, description stages of human development according Al-Qur'an, and comparison with Western views. The method used in this study is Qualitative Study. Results of the study indicate that Islam views human development holistically, encompassing physical, psychological, spiritual, and moral aspects. In contrast to Western theories that emphasize cognitive and psychosocial aspects, Islam emphasizes the goal of development as an effort to achieve happiness in this world and hereafter. Al-Qur'an describes stages of human life in detail, from the process of creation to maturity and old age, even to the post-mortem phase. This study shows that Islamic concept of human development can be an important foundation in education and character development based on divine values